Perilaku Konsumtif Mahasiswa Pendidikan Ekonomi sebagai Dampak Perkembangan E-Commerce - Nurjannah Nurjannah; Nurdiana Nurdiana; Andi Tenri Ampa (Universitas Negeri Surabaya, 2023)
This study aims to analyze the consumptive behavior of Makassar State University Economics Education students in E-Commerce. This research is a descriptive qualitative research using primary data directly taken from informants by way of observation and interviews. The determination of the sample used was Snowball Sampling with 3 informants from Batch 2022 of the Economics Education Study Program, Faculty of Economics, Makassar State University. The results of the study show that the main reason for Economic Education students class of 2022 to make purchases through e-commerce is due to several things, namely, practicality, many choices and considerations for prices and promos given to the online store.